THE STANDARDIZATION OF CORPORATE GOVERNANCE POLICIES ACROSS STATE-OWNED ENTERPRISES IN LIBERIA, WEST AFRICA - Toneah Gblee, Isaac (Global journal of Business and Integral Security, 2023)
This research has focused on how the use of standardized corporate governance policies across state-owned enterprises in Liberia, West Africa leads to better performance and increased revenue generation capacity and creates more financially stable and sustainable enterprises. Across these state-owned enterprises, the research has sought to identify the existence of core corporate governance components, such as appropriate Board composition and mix of skills, Board procedures, directors’ remunerations in line with best practice, code of business ethics, internal control procedures, risk management framework, disaster recovery system, business continuity procedures, appointment of an internal auditor and independent external auditors, an independent audit committee, management information systems, compliance framework, Board corporate governance committee and improvement plan, formalized corporate governance policies and procedures and code, Board accountability to shareholders and management accountability to the Board, timely accurate disclosure of all material matters, financial statements prepared in accordance with international IPSAS, high-quality and transparent financial annual reports, independent non-executive Board members and advisers, conduct of shareholder meetings, policies on related party transactions and extraordinary transactions, clearly defined and explicit dividend policies, and clear definition of roles and authorities of stakeholders. The study demonstrates the importance of good corporate governance policies across state-owned enterprises in Liberia and describes existing processes of corporate governance policies in Liberia state-owned enterprises. It has analyzed the reasons for the collapse of some state-owned enterprises in Liberia, mainly due to inadequate or insufficient compliance with good corporate governance standards. Additionally, this research has investigated how the collapse of these Liberia state-owned enterprises could have been averted by ensuring good corporate governance practices. The research investigated these problems and sought to point out the many challenges as well as benefits of standardizing corporate governance policies across state-owned enterprises in Liberia. These challenges and others have been treated in this research and appropriate recommendations made for the consideration of relevant Liberian policymakers.